Occupational therapy roles and responsibilities: Development of a standardised measure of time use for staff working with adults in community settings. (June 2016) - Hughes, Jane; Wilberforce, Mark; Symonds, Eileen; Bowns, Ian; Challis, David
Introduction: This paper documents the development of a diary schedule to describe the work of occupational therapists of all grades, across a range of adult care groups and community health and social care settings, to permit comparison between them and over time. Method: Two sources of information were used to develop the schedule: findings from five focus groups with occupational therapists (46 participants) and analysis of previous research on staff time use undertaken by the Personal Social Services Research Unit at the University of Manchester. It was piloted and evaluated by scrutiny of the schedules, a group interview with participants and meetings with managers. Results: Practitioners identified almost 200 activities in their day-to-day work. These were categorised into three principal activity themes: direct care, indirect care and team or service development. The pilot study revealed ease of completion and discernible differences between settings and activities together with suggestions for improvement to the schedule regarding the description of activities and the accompanying guidance. Conclusion: A diary schedule and common activity list, covering the full breadth of occupational therapy practice in adult community care, was developed. Whilst its utility in an organisation employing practitioners in multiple settings was demonstrated its wider applicability is unproven.